Development and the temporality of its exchange: How an Eastern Yucatec village made cash transfer promises accountable - Dapuez, Andres Francisco (2016)
This paper explores how three temporalities of exchange amend the reception of cash transfers for development in a village in Eastern Yucatan, Mexico. Based on participant observation and in-depth interviews of recipients of cash transfers from Procampo and Oportunidades, this study reveals that ritual promising functions as a means of temporal regulation in most transactions of this sort, and that the recipients hold their government accountable for promises and commitments regarding cash transfers. In assessing the temporal ranges and effectiveness of these transfers by alluding to previous stipulations that sustain the exchange and make it understandable and bearable as a promise, the people in this village consider the objectives of the Procampo and Oportunidades programs to be implausible. Accountability with respect to the long-term effects of these transfers is not, however, based only on local impressions of a state that procrastinates in its “engagement” with peasants. As the timetable established for the accumulation of human capital also exceeds the time limits of responsible promising, these cash transfer programs cannot be evaluated in terms of their fulfilled or unfulfilled promises.